2007
DOI: 10.1093/annonc/mdm106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subcentimeter nonpositive resection margin on hepatic recurrence in patients undergoing hepatectomy for colorectal liver metastases. Evidences from 663 liver resections

Abstract: Subcentimeter nonpositive resection margins do not directly influence hepatic recurrence in patients undergoing hepatectomy for colorectal liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 30 publications
4
78
2
3
Order By: Relevance
“…More wedge resections can be performed because several recent studies have indicated that a margin less than 1 cm is not a contraindication to resection of colorectal liver metastases. [22][23][24][25] Moreover, a margin of 1 mm seems to be appropriate, despite the fact that the pathological report will define the procedure as a microscopic irradical resection. 24 Current techniques with ultrasonic dissectors aspirate a part of the liver parenchyma interposed between the specimen and the normal liver, making assessment of the true margin difficult.…”
Section: Discussionmentioning
confidence: 99%
“…More wedge resections can be performed because several recent studies have indicated that a margin less than 1 cm is not a contraindication to resection of colorectal liver metastases. [22][23][24][25] Moreover, a margin of 1 mm seems to be appropriate, despite the fact that the pathological report will define the procedure as a microscopic irradical resection. 24 Current techniques with ultrasonic dissectors aspirate a part of the liver parenchyma interposed between the specimen and the normal liver, making assessment of the true margin difficult.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time the ideal margin is yet to be defined as some authors have shown that negative margins of either 1-4 mm, 5-9 mm or up to 1 cm have similar overall recurrence rates and survival [25][26][27] . In our study differences in recurrence and survival could not be found when comparing free surgical margins under and above 1 cm, a fact that supports these previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of some conflicting reports, evidence shows that size is not a resectability factor, but a factor related to the aggressiveness of the tumour. Likewise, the width of the surgical margin has no effect on survival providing that the margin is microscopically negative [128][129][130] , though resection should attempt to get an optimum margin.…”
Section: Resectabilitymentioning
confidence: 99%